2013
DOI: 10.1016/j.jhe.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of neighborhood characteristics in mortgage default risk: Evidence from New York City

Abstract: Using a rich database of non-prime mortgages from New York City, we find that census tract level neighborhood characteristics are important predictors of default behavior, even after controlling for an extensive set of controls for loan and borrower characteristics. First, default rates increase with the rate of foreclosure notices and the number of lender-owned properties (REOs) in the tract. Second, default rates on home purchase mortgages are higher in census tracts with larger shares of black residents, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
6
28
0
Order By: Relevance
“…It cannot conclusively be determined from this study that discrimination accounts for the large negative disparity in lending between minority and white neighborhoods. Past research has found neighborhood racial composition to be a proxy for both unobserved characteristics and very local economic conditions (Chan et al 2010). Established minority neighborhoods are typically located in central cities where housing stock is older and more likely to be multiunit, such as two or four family homes (Munnell et al 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It cannot conclusively be determined from this study that discrimination accounts for the large negative disparity in lending between minority and white neighborhoods. Past research has found neighborhood racial composition to be a proxy for both unobserved characteristics and very local economic conditions (Chan et al 2010). Established minority neighborhoods are typically located in central cities where housing stock is older and more likely to be multiunit, such as two or four family homes (Munnell et al 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Other unobserved reasons for variations in credit offered which may be correlated with neighborhood racial composition or borrower race include loan-to-value ratio, housing indebtedness, wealth, job history, and stability of income or employment and condition of the property (Berkovec et al 1994;Calem, Gillen, & Wachter 2004;Pedersen and Delgadillo 2007). The mortgage industry treats nonblack neighborhoods differently from black neighborhoods because of borrower and loan characteristics that are both more prevalent in black neighborhoods and correlated to higher default risk (Chan et al 2010). Van Order and Zorn (2000) confirm the higher the neighborhood black population, the higher the default risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter methodology outperforms reverse regression. Finally, Chan et al (2011) relate the 90-day mortgage default rate available in HDMA data to neighborhood characteristics, hence highlighting possible sources of redlining.…”
Section: Annotated Bibliographymentioning
confidence: 99%
“…The literature indicates, in general, that residential mortgage foreclosures concentrate in low-income minority neighbourhoods, and thus, without policy and redevelopment intervention, housing stock and neighbourhoods might not be desirable for quality affordable housing (Apgar & Duda, 2004;Immergluck & Smith, 2006a, 2006bBelsky, 2008;Bocian et al, 2008;Chan et al, 2010). On the other hand, condominium foreclosures might provide quality affordable housing opportunities without redevelopment.…”
Section: Condominium Foreclosure and Providing Quality Affordable Houmentioning
confidence: 99%